Profile of medication use during pregnancy: Results of the BRISA study, São Luís - MA, Brazil (Research, Society and Development, 2022)
Objectives: To describe the medication profile used during pregnancy in a Brazilian capital. Methods: Descriptive cross-sectional study with data from BRISA study in São Luís, Maranhão. Participants were interviewed in hospitals and maternity hospitals after delivery and were asked about the use of medications during pregnancy. The drugs were classified according the Anatomical Therapeutic Chemical Classification and risk categories of the Food and Drug Administration. Results: 5,110 puerperal women were interviewed, of which 93.5% reported the use of at least one medication during pregnancy. The most frequent medications were: antianemic preparations (ferrous sulfate: 72.2%; iron and multivitamins: 4.9%, folic acid: 62.9% and associations with folic acid: 6.7%), vitamins (multivitamins and others minerals: 30.3%), analgesics (paracetamol: 12.3%), antibacterials for systemic use (cephalexin: 5.6%), antiemetics and anti-nauseating agents (scopolamine butylbromide: 5.4%) and antihypertensives (methyldopa): 3.6%). Among the drugs reported: 74.5% were from category A, 18.9% from category B, 5.5% from category C, 1.0% from category D and 0.1% from category X. Conclusions: Despite, the higher prevalence of medication use during pregnancy, most of which are considered safe in pregnancy. However, it is important that the use of drugs during pregnancy is monitored and guided by health professionals in order to ensure its rational use.